Note:
Your question is a little unclear. But, from my understanding, I assume you may be asking the evaluation of the expression 36x - y when x = 3 and y = -6.
so I will solve based on my assumption which anyways would clear your concept.
Answer:
The value of 36x - y when x = 3 and y = -6 will be: 114
Explanation:
Given
Assuming the expression
36x - y
To Determine
Evaluate 36x - y when x = 3 and y = -6
Given the expression
substitute x = 3 and y = -6 to evaluate the expression
Therefore, the value of 36x - y when x = 3 and y = -6 will be: 114